Dampak Coaching pada Karyawan di Perusahaan: Sebuah Tinjauan Literatur - Dwi Rahma Elysia; Calista Giseila Gitafreya; Aliya Syakira Putri Fanani; Delta Putri Anggiyani (Universitas Palangka Raya, 2026)
In an era of increasingly competitive business competition, companies are required to improve the quality of their human resources to achieve optimal organizational performance. One approach widely used in employee development is coaching. This study aims to examine the implementation of coaching for employees in companies and its impact on employee performance and development. This study used the Systematic Literature Review (SLR) method following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The literature search process was conducted through several scientific databases, namely Google Scholar, Scopus, and the Directory of Open Access Journals (DOAJ) with a publication period of 2021–2026. Keywords used included coaching, employee coaching, employee performance, and employee development. Based on the literature selection process, 16 articles met the inclusion criteria and were further analyzed. The results showed that the implementation of coaching has a positive impact on improving employee performance, work motivation, self-confidence, and individual competency development. Furthermore, coaching also plays a role in increasing employee work engagement, communication skills, and self-awareness in completing work tasks. These findings indicate that coaching is an effective strategy in human resource development and improving organizational performance if applied systematically, while also providing practical contributions for HR practitioners in designing measurable and sustainable talent development interventions.